If You Give a Pig a Party - Numeroff, Laura Joffe; Bond, Felicia (New York : Laura Geringer Books, 2005)
One thing leads to another when you give a pig a party.
a"An if you give-- book"--Jacket.
Preschool-Grade 2.
Keywords: Pigs -- Fiction; Animals -- Fiction